2012
DOI: 10.1002/hed.23201
|View full text |Cite
|
Sign up to set email alerts
|

Characteristics of radiation-induced sensorineural hearing loss in head and neck cancer: A systematic review

Abstract: High quality literature in the topic is lacking. Radiation-induced SNHL is progressive, permanent, and dose-dependent. Total dose and follow-up time are important factors affecting incidence rates.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

5
60
2
6

Year Published

2014
2014
2021
2021

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 61 publications
(73 citation statements)
references
References 34 publications
5
60
2
6
Order By: Relevance
“…Investigators described that platinnun drugs affected 14% of cancer treatment´s survivors once these drugs are considered not only ototoxic, but neurotoxic [15]. The incidence of hearing loss for head and neck cancer, in our study was 28.8% therefore investigators reported an incidence of 27% to 95% [13].…”
Section: Discussionsupporting
confidence: 45%
See 2 more Smart Citations
“…Investigators described that platinnun drugs affected 14% of cancer treatment´s survivors once these drugs are considered not only ototoxic, but neurotoxic [15]. The incidence of hearing loss for head and neck cancer, in our study was 28.8% therefore investigators reported an incidence of 27% to 95% [13].…”
Section: Discussionsupporting
confidence: 45%
“…There is a variability of hearing loss incidence, once it has influence of radiation technique (2D or 3D) and dose, anticancer drugs and dose, individual susceptibility and age [3,13]. In our research, all patients received, and 3D radiotherapy as prescribed by oncologist.…”
Section: Discussionmentioning
confidence: 93%
See 1 more Smart Citation
“…The permanent effect of radiotherapy on hearing is sensorineural hearing loss (SNHL) caused by radiation damage to the inner ear. 5 However, intensitymodulated radiotherapy may spare the cochlea the effects of high-dose radiotherapy, thereby reducing the incidence of radiotherapy-induced SNHL. 6 Apart from radiotherapy, cisplatin is also known to cause permanent SNHL starting immediately after the first cisplatin infusion.…”
mentioning
confidence: 99%
“…[5,6] and it was observed that patients who had hearing loss primarily had bilateral symmetric sensorineural hearing loss [7]. Moreover, one recent systematic review has also indicated that patients receiving radiotherapy for head and neck tumors could be at risk of developing sensorineural hearing loss, although high-quality research is still lacking [8]. Genes such as DFNA5 could also play a role in the etiology of hearing loss while involving cancer [9].…”
Section: Main Findingsmentioning
confidence: 99%